Students’ Attitude towards Online Learning: Its Impact to Students’ Problem-Solving Ability - Ariel Berico; Arnel Travero (Universitas Sarjanawiyata Tamansiswa, 2023)
This study assessed the relationship of attitude towards online learning on the problem-solving ability of 2nd year Bachelor of Elementary Education (BEED) students of Don Carlos Polytechnic College. It aimed to describe the level of students’ attitude toward online learning; ascertain the problem-solving ability of the students; correlate students’ problem-solving ability with the attitude toward online learning; and identify which component of attitude towards online learning best impacts and predicts students’ problem-solving ability. A descriptive-correlational research design was used in this study. Mean, correlation and regression analyses were employed. Students were found to have positive attitude towards online learning; however, their problem-solving ability is still very poor. Moreover, there was a significant relationship on students’ attitude towards online learning, specifically on ease-ness in using online learning, on students’ problem-solving ability. Further, it was revealed that problem-solving ability is predicted by ease-ness in using online learning. Nevertheless, due to the limited scope of this work, the authors felt that there is a need for more extensive research particularly in the effectiveness of online learning to arrive at conclusions that would be more valid, and applicable to a larger student population.